Methods of Social Interaction Learning for Students of Non-Profit Organizations - Gubarenko, Irina V.; Kovalenko, Viktor I.; Kovalenko, Elena V.; Miyusov, Vladislav A.; Sokolova, Olga A. (International Journal of Criminology and Sociology, 2022)
Search and substantiation of new form productivity for student non-formal education, which make it possible to compensate for the deficit of purposeful preparation for social interaction in the traditional (formal) system of higher education. Methodology: system-dialectical approach, which allows to overcome the existing fragmentation and the fragmentation of research results concerning the experience of student social interaction; the methods of scientific analysis of sources; pedagogical experience study; comparative analysis; classification; content analysis; mathematical processing of statistical data. Results: they substantiate the relevance of addressing social education of students in youth non-profit organizations, as one of the forms of non-formal education. The individual and group experience of social interaction and its promising lines of enrichment (subjectivity, reflexivity, co-existence) are proposed as a system-organized educational result. The content of education is determined based on the characteristics of social practices implemented in non-profit organizations. The results of the comparative study of the applied forms and methods of youth training in existing youth non-profit organizations in Russia and abroad (the Association of Trainers of the Russian Union of Youth, the All-Russian School of Personal Growth and Development of Student Self-Government "Progress", "The College of Trainers by T. Hoist" (Germany), "Freechild Institute" (USA). The methods of social training of their participants most widespread in non-profit organizations, the features and results of their application are determined. The conclusions are made about the relevance and prospects of student youth preparation optimization for active social interaction in non-formal education within the context of non-profit organizations based on the methodology of the system-dialectical approach to the enrichment of individual and group experience of social interaction.